Understanding circular economy awareness and practices in manufacturing firms. Issue 4 (10th June 2019) - Liakos, Nikolaos; Kumar, Vikas; Pongsakornrungsilp, Siwarit; Garza-Reyes, Jose Arturo; Gupta, Bhumika; Pongsakornrungsilp, Pimlapas
Abstract : Purpose: Circular economy (CE) has evolved as a result of the growing environmental awareness, environmental legislation and the need for social responsibility. However, awareness levels of CE are not as high as expected and practices are further behind than they should be, with a significant lack of research around the subject in the literature. Therefore, the purpose of this paper is to examine the current state of awareness levels and the practices around CE in manufacturing firms. Moreover, the study aims to empirically validate one of the earlier proposed CE models. Design/methodology/approach: The study adopts a quantitative survey questionnaire based approach. More than 500 people from various manufacturing organisations were contacted directly over a 40-day long sampling process through the FAME database, personal contacts and LinkedIn. The survey resulted in 103 completed responses. Given the exploratory nature of the study, the data were mainly analysed using descriptive statistics. To validate the CE model, a correlation analysis was also conducted. Findings: The research findings show that with the growing emphasis on CE across the globe by governing bodies, firms are becoming more aware of CE practices. The analysis also shows some useful insights on the state of each of the pillars (economic benefits, environmental impact and resource scarcity) of CE. The findings also indicate that the environmental impact pillar of CE is at a more developed state than the other two pillars which are, mostly, in a research state. Research limitations/implications: The study provides manufacturing firms with a thorough understanding of the state of CE practices and importance of its successful implementation. The findings of the study advocates consideration of all three pillars of CE by managers as a guide to plan for an efficient strategy around CE implementation. Moreover, our study adds to existing efforts by the academic community to raise the awareness towards CE practice among all relevant stakeholders. The findings of this study are based on the responses from a limited 103 survey responses from manufacturing firms. Originality/value: This study adds to the very limited empirical literature on CE awareness and practices in manufacturing firms. This is also one of the first studies attempting to empirically validate an existing CE model.